Comparison of physical properties enhancement in various heat transfer nanofluids by MXene - Samylingam, Lingenthiran; Kadirgama,, Kumaran; Aslfattahi, Navid; Samykano, M. (Elsevier, 2022)
Advancements in the formulated nanofluids have led to the dominant technologies to consider these superior heat transfer fluids significantly. Extensive studies related to the enhanced physical properties of nanofluids are performed in order to promote the acquired advancements in nanofluids heat transfer. This chapter aims to give a comprehensive comparison between the highly efficient formulated nanofluids with the incorporation of MXene as a promising additive. Various types of developed nanofluids with improved physical properties due to the inclusion of MXene nanomaterial are considered as the main focus of this chapter in order to provide insightful perceptions related to the achieved advances in the formulated heat transfer nanofluids. Physical properties such as thermal conductivity, viscosity, and thermal stability are considered for the conducted comparative study related to the advances in nanofluids with the presence of MXene. The highest thermal conductivity enhancement of ~176% was acquired for the formulated palm oil methyl ester/MXene heat transfer nanofluid.